Simulação molecular da adsorção de hidrocarbonetos em aluminofosfatos - Lucena, Sebastião Mardonio Pereira de (2006)
Orientadores: João Alexandre Ferreira da Rocha Pereira, Celio Loureiro Cavalcante Junior